Transcranial Direct Current Stimulation (tDCS) to Improve Gait in Multiple Sclerosis: A Timing Window Comparison - Workman, Craig D.; Kamholz, John; Rudroff, Thorsten (Frontiers in Human Neuroscience, 2019)
Unilateral weakness of the lower limb is a hallmark of multiple sclerosis (MS) and a significant contributor to the progressive worsening of walking ability. There are currently no effective rehabilitation strategies targeting strength asymmetries and/or gait impairments in people with MS (PwMS). Transcranial direct current stimulation (tDCS) has previously improved motor outcomes in various populations, but the effect of tDCS on gait in PwMS and the ideal timing window of tDCS application are still unknown. This study investigated the effects of tDCS, either before or during a 6 minute walk test (6MWT), on the distance walked, and the gait characteristics, in PwMS. 12 participants were recruited and randomly assigned into BEFORE or DURING groups (both n = 6). The BEFORE group received stimulation before performing a 6MWT (sham/2 mA, 13 min), while the DURING group received stimulation only during a 6MWT (sham/2 mA, 6 min). Stimulation was over the more MS-affected primary motor cortex.Distance walked and gait characteristics of the walk were the primary and secondary outcomes.The results indicated a significant decrease in distance walked in the DURING group (p = 0.026) and a significant increase in gait velocity in the BEFORE group (p = 0.04). These changes were accompanied by trends (p < 0.1) in distance walked, gait velocity, and stride length in the same direction as the significant results for each group. Overall, the results of this study suggest that tDCS performed before a 6MWT might be more effective than tDCS during a 6MWT.